‘They know to whom they can do it … ’ democratic inequality and the policing of urban peripheries in Chile - García-Campo Almendros, Gonzalo (Policing and society, 2025)
This article examines how contrasting patterns of policing in marginalised neighbourhoods exacerbate social inequalities, ultimately undermining the core tenets of democratic policing. Viewed through the lens of democratic egalitarianism, the research shows how these patterns – characterised by surveillance and control in some areas and neglect of residents’ concerns in others – converge to erode the normative aspiration of building egalitarian social relations. Drawing on in-depth interviews with 21 residents from two marginalised communities in Chile, this study prioritises the lived experiences of marginalised people. The analysis reveals how residents’ interpretations of these contrasting police responses and their expectations of the police reinforce their sense of marginalisation. By applying the theoretical framework of democratic equality, this work contributes to the ongoing discourse on achieving democratic policing. It sheds light on the real-world consequences of policing practices that perpetuate social inequalities.